10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Contemporary nursing practice increasingly takes place within culturally, religiously, and ethically plural healthcare environments. Although professional standards provide a shared ethical foundation, limited conceptual attention has been given to how nurses' religious moral identities influence ethical reasoning during cross-gender care. Existing discussions of professionalism remain largely grounded in secular ethical perspectives, leaving insufficient exploration of how faith-based moral traditions may contribute to professional identity and moral agency. This paper examines gender interaction in nursing through Islamic ethical perspectives and proposes a conceptual framework of faith-informed professionalism to contribute to broader discussions of ethical pluralism in nursing ethics. A conceptual normative analysis was undertaken through critical engagement with literature on nursing professionalism, moral agency, ethical pluralism, and Islamic ethics. Relevant concepts were identified, interpreted, and synthesised to develop a conceptual framework integrating professional standards with Islamic ethical principles relevant to gender interaction in nursing practice. The analysis argues that gender interaction should be understood not only as a matter of professional conduct but also as an ethically significant encounter in which Muslim nurses negotiate professional responsibilities alongside religiously informed moral commitments. Drawing on the concepts of haya', adab, niyyah, ikhtilat, darurah, and maqasid al-shariah, the paper develops faith-informed professionalism as a conceptual framework that explains how faith-based moral commitments may coexist with professional standards while maintaining patient welfare, professional accountability, and equitable care as overriding priorities. A clinical illustration demonstrates the framework's application as a guide for ethical reflection rather than a prescriptive model for practice. Faith-informed professionalism extends contemporary discussions of moral agency, professional identity, and ethical pluralism by recognising that religious moral traditions may complement, rather than compete with, established professional standards. The proposed framework offers a theoretical contribution to nursing ethics and provides a foundation for future empirical research and educational development within multicultural healthcare environments.